(untitled) (Research, Society and Development, 2023)
Burnout Syndrome comes from English and means "burn out" or "burn out to the end". When we talk about this problem in nursing professionals, it is notorious how several factors contribute to the emergence of cases in this professional class. The services provided by nursing professionals in Intensive Care Units - ICU’s demonstrate to be even more prone to the emergence of cases of the disorder, given the intense and constant routine experienced by professionals. Thus, this study aims to analyze the problem of Burnout Syndrome in nursing professionals in the Intensive Care Unit, as well as to understand its symptoms and triggering factors. The study is an integrative literature possible to discover that a major determinant of all these causes and the development of several associated pathologies is stress and that it has key symptoms such as high levels of emotional exhaustion, depersonalization, and low professional fulfillment. Finally, multiple factors contribute to the emergence of new cases of the disorder, considering the stressful and hostile environment that is present in the nursing professional’s routine. The high workload, limited staff and the complexity of the procedures are triggers for the emergence of the Burnout Syndrome.